Adaptive fuzzy multivariable controller design based on genetic algorithm for an air handling unit. (1st March 2015) - Khan, Muhammad Waqas; Choudhry, Mohammad Ahmad; Zeeshan, Muhammad; Ali, Ahsan
Abstract: In HVAC (Heating, Ventilation and Air Conditioning systems, effective thermal management is required because energy and operation costs of buildings are directly influenced by how well an air-conditioning system performs. HVAC systems are typically nonlinear time varying with disturbances, where conventional PID controllers may trade-off between stability and rise time. To overcome this limitation, a Genetic Algorithm based AFLC (Adaptive Fuzzy Logic Controller design has been proposed for the multivariable control of temperature and humidity of a typical AHU (air handling unit by manipulating valve positions to adjust the water and steam flow rates. Modulating equal percentage Globe valves for chilled water and steam have been modeled according to exact flow rates of water and steam. A novel method for the adaptation of FLC (Fuzzy Logic Controller by modifying FRM (Fuzzy Rule Matrix based on GA (genetic algorithm) has been proposed. This requires re-designing the complete FLC in MATLAB/Simulink whose procedure has also been proposed. The proposed adaptive controller outperforms the existing fuzzy controller in terms of steady state error, rise time and settling time. Highlights: GA based Adaptive Fuzzy Logic Controller to improve performance of HVAC system. Multivariable control of an air handling unit to adjust the water and steam flow rates. Significant improvement in steady state error, rise time and settling time of the control system.